Pathophysiological mechanisms of thrombosis in acute and long COVID-19 - Jing, Haijiao; Wu, Xiaoming; Xiang, Mengqi; Liu, Langjiao; Novakovic, Valerie A.; Shi, Jialan (Frontiers in Immunology, 2022)
COVID-19 patients have a high incidence of thrombosis, and thromboembolic complications are associated with severe COVID-19 and high mortality. COVID-19 disease is associated with a hyper-inflammatory response (cytokine storm) mediated by the immune system. However, the role of the inflammatory response in thrombosis remains incompletely understood. In this review, we investigate the crosstalk between inflammation and thrombosis in the context of COVID-19, focusing on the contributions of inflammation to the pathogenesis of thrombosis, and propose combined use of anti-inflammatory and anticoagulant therapeutics. Under inflammatory conditions, the interactions between neutrophils and platelets, platelet activation, monocyte tissue factor expression, microparticle release, and phosphatidylserine (PS) externalization as well as complement activation are collectively involved in immune-thrombosis. Inflammation results in the activation and apoptosis of blood cells, leading to microparticle release and PS externalization on blood cells and microparticles, which significantly enhances the catalytic efficiency of the tenase and prothrombinase complexes, and promotes thrombin-mediated fibrin generation and local blood clot formation. Given the risk of thrombosis in the COVID-19, the importance of antithrombotic therapies has been generally recognized, but certain deficiencies and treatment gaps in remain. Antiplatelet drugs are not in combination with anticoagulant treatments, thus fail to dampen platelet procoagulant activity. Current treatments also do not propose an optimal time for anticoagulation. The efficacy of anticoagulant treatments depends on the time of therapy initiation. The best time for antithrombotic therapy is as early as possible after diagnosis, ideally in the early stage of the disease. We also elaborate on the possible mechanisms of long COVID thromboembolic complications, including persistent inflammation, endothelial injury and dysfunction, and coagulation abnormalities. The above-mentioned contents provide therapeutic strategies for COVID-19 patients and further improve patient outcomes.